This preview shows page 1. Sign up to view the full content.
Unformatted text preview: tions, and the PDE becomes: v t + w t = k ( v xx + w xx ) Since w t = w xx = 0, we can write the PDE v t = kv xx The initial condition is v ( x, 0) + w ( x, 0) = 0 or v ( x, 0) = − x − 1 So the problem is now: v t = kv xx v (0 , t ) = 0 v x ( L, t ) = 0 v ( x, 0) = − x − 1 85...
View
Full
Document
This note was uploaded on 12/22/2011 for the course MAP 2302 taught by Professor Bell,d during the Fall '08 term at UNF.
 Fall '08
 BELL,D

Click to edit the document details